2013
DOI: 10.1021/pr301073j
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Immobilized Kinase Inhibitors and Covalent ATP Probes for Proteomic Profiling of Kinase Expression and Drug Selectivity

Abstract: Kinases are involved in the regulation of many cellular processes and aberrant kinase signaling has been implicated in human disease. As a consequence, kinases are attractive drug targets. Assessing kinase function and drug selectivity in a more physiological context is challenging and often hampered by the generally low expression level of kinases and the extensive post-translation modification in vivo. Kinase drug selectivity screens by chemical proteomics have gained attention because they allow the profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 49 publications
4
54
0
Order By: Relevance
“…First, we cannot ensure the entire kinome is being covered by the desthiobiotin-ATP probe used in our studies, which could be limited by the low abundance of certain kinases or the sequences not having a solvent accessible lysine near the active site. Nonetheless, we identified 196 protein kinases in H82 cells and 179 protein kinases in SW210.5 cells, which compares favorably with other reports that employ ABPP (28, 29). However, using these probes results in a certain bias toward serine/threonine kinases over tyrosine kinases compared to approaches with immobilized kinase inhibitors.…”
Section: Discussionsupporting
confidence: 87%
“…First, we cannot ensure the entire kinome is being covered by the desthiobiotin-ATP probe used in our studies, which could be limited by the low abundance of certain kinases or the sequences not having a solvent accessible lysine near the active site. Nonetheless, we identified 196 protein kinases in H82 cells and 179 protein kinases in SW210.5 cells, which compares favorably with other reports that employ ABPP (28, 29). However, using these probes results in a certain bias toward serine/threonine kinases over tyrosine kinases compared to approaches with immobilized kinase inhibitors.…”
Section: Discussionsupporting
confidence: 87%
“…This notion is further substantiated by the fact that 44% of the identified spectra from the ATP probe experiment belong to proteins with documented nucleotide binding activity, whereas this figure is only 12% in the experiment using kinobeads. In keeping with this finding, the authors also observed that increasing the amount of input material facilitated the detection of more kinases using kinobeads; however, increasing the lysate amount beyond 1 mg in experiments using the ATP/ADP probes led to identification of a large proportion of proteins which were labeled through non‐specific interactions (Lemeer et al, ). Moreover, a significantly larger number of tyrosine kinases were enriched using kinobeads, whereas members of the STE kinase group (mainly the MAP kinases) were better represented with the use of the ATP probes.…”
Section: Global Kinome Enrichment/detection Platforms and Their Applimentioning
confidence: 82%
“…Other studies used the KinoBead approach to profile changes in the baseline kinome of different cancer cell lines and other cells [Oppermann et al, 2009;Gholami et al, 2013;Medard et al, 2015]. Interestingly, a high degree of complementarity between these two methods was observed in these studies [Lemeer et al, 2013]. However, no claims were made regarding the ability of these reagents to measure the actual activation state of individual kinases in the kinome.…”
Section: Kinobeadsmentioning
confidence: 99%